The effects of previous cesarean deliveries on severe maternal and adverse perinatal outcomes at a university hospital in Tanzania. Issue 2 (May 2016) - Litorp, Helena; Rööst, Mattias; Kidanto, Hussein L.; Nyström, Lennarth; Essén, Birgitta
Abstract: Objective: To investigate if multiparous individuals who had undergone a previous cesarean delivery experienced an increased risk of severe maternal outcomes or adverse perinatal outcomes compared with multiparous individuals who had undergone previous vaginal deliveries. Methods: An analytical cross-sectional study at a university hospital in Dar es Salaam, Tanzania, enrolled multiparous participants of at least 28 weeks of pregnancy between February 1 and June 30, 2012 . Data were collected from patients' medical records and the hospital's obstetric database. Odds ratios (OR) and 95% confidence intervals (CI) were calculated to compare outcomes among patients who had or had not undergone previous cesarean deliveries. Results: A total of 2478 patients were enrolled. A previous cesarean delivery resulted in no increase in the risk of severe maternal outcomes (OR 0.86, 95% CI 0.58–1.26; P = 0.46), and decreased risk of stillbirth (OR 0.42, 95% CI 0.29–0.62, P < 0.001), and intrapartum stillbirth and neonatal distress (OR 0.58, 95% CI 0.38–0.87, P = 0.007). Conclusion: Previous cesarean delivery was not a risk factor for severe maternal outcomes or adverse perinatal outcomes. The present study was conducted at a referral institution, where individuals with previous cesarean deliveries may constitute a healthy group. Additionally, there could be differences between the study groups in terms of healthcare-seeking behavior, referral mechanisms, intrapartum monitoring, and clinical decision making.